0218 Effects Of Sleep Deprivation And Recovery Sleep On Human Brain Network Organization. (27th April 2018) - Jiang, Y; Chai, Y; Yang, F; Xu, S; Basner, M; Detre, J A; Dinges, D F; Rao, H
Abstract: Introduction: Sleep plays a key role in the restoration and preservation of optimal brain function, whereas sleep loss causes fatigue and impairs a range of neurobehavioral functions. Accumulating evidence suggests that the human brain can be characterized as a small-world network. However, the effects of sleep deprivation (SD) and recovery sleep on human brain network organization remain unclear. Here we used resting-state functional magnetic resonance imaging (fMRI) to evaluate changes in brain network topology after sleep deprivation. Methods: We used graph theory to analyze resting-state fMRI data from 51 health adults (34.1 ± 9.0y, 29 males) who participated in a 5-day and 4-night in-laboratory controlled study. Thirty-eight participants completed an experimental protocol including 36-hour acute total SD (TSD) after one night of 9-hour baseline sleep, and followed by two nights of recovery sleep. They were scanned three times on the mornings of day 2 after baseline sleep, day 3 during SD, and day 5 after recovery sleep. Thirteen participants completed a non-SD control protocol and were scanned three times on the equivalence days. Three network metrics, including small-worldness (σ), global efficiency, and local efficiency were calculated for each subject using GRETNA toolbox and compared between baseline, SD, and recovery conditions. Results: All three brain network metrics were significantly reduced after one night of TSD compared to baseline (all p <0.001). After two nights of recovery sleep, network small-worldness and global efficiency returned to baseline level, whereas local efficiency was not fully restored to baseline level. Brain network small-worldness and global efficiency changes correlated with self-reported fatigue level increases during sleep loss (both p <0.005). No changes in brain network metrics were found among the fMRI scans in the control group. Conclusion: Our results suggest that one night of TSD significantly impairs topological properties of brain small-world network. Two nights of recovery sleep fully restored global but not local properties of brain network organization. Support (If Any): Supported in part by NIH grants R01-HL102119, R01-MH107571, R01-NR004281, CTRC UL1RR024134, P30-NS045839, and the PENN IOA Pilot Project.